Pitfalls In The Diagnosis Of Primary Headaches - Ravishankar K (Annals of Indian Academy of Neurology, 2002)
Inspite of the fact that headache is one of the most common medical complaints, most headaches in practice continue to be underdiagnosed and undertreated. Probably because most of the recent advances in headache are written in rare speciality journals. Even today many treating physicians feel that nothing much can be done for headache patients! And, since more than 90% of headaches seen in practice are primary headaches, it is to be realised that matters have come a long way in the last decade and these is now enough evidence to prove that primary headaches are a genuine potentially treatable biological problem. It is therefore important that clinicians do not err in making the right diagnosis and choosing the correct drug options. This article discusses some of the traps which may result in the sub-optimal management of primary headaches and suggests measures to avoid these ′Pitfalls′.